Urban Development and Transportation: Investigating Spatial Performance Indicators of 12 European Union Coastal Regions - Nikolaou, Paraskevas; Basbas, Socrates (My University, 2023)
Urbanization is one of the most dominant economic and social changes of the 20th century. This phenomenon brings about rapid urban development, which is inextricably linked to transport development. In order to understand this relationship, it is important to analyze the spatial spillover effects of the phenomenon in the urban environment. This study analyzes the spatial performance, in terms of urban development, of 12 European Union regions from five European countries with coastal areas by incorporating spatial data such as length of road network, population distribution, land uses, and other factors. Key performance indicators have been developed for evaluating the structural development model of the regions (e.g., dense or sprawl development). In addition, the incorporation of spatial spillover effects in the evaluation of the regions was conducted by the extended spatial data envelopment analysis (SDEA) method. The results of SDEA identified the best and worst-performing regions in terms of urban growth. Finally, this study implements a target-setting approach where under-performing regions can best perform. Based on the target-setting approach, local authorities can set realistic targets for improving the structural model that the regions are following.
Keywords: urban development; spatial data envelopment analysis; transportation infrastructure; key performance indicators; target setting